Career Information Services by Using Interactive Multimedia to Determine Students Career Choices - Salimah, Hanum; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2019)
This study aimed to determine the effectiveness of career information services by using Android-based interactive multimedia to help to determine students’ career choices. Meanwhile, the method used was experimental research using One Group Pre-test – Post-test Design. For more, the subjects of this study were chosen randomly (using random sampling) from 35 students of the Tenth Grade Level or Class X of Senior High School (SMA) 1 Kudus. The hypotheses of this study which were tested by using t-test paired samples showed that there was an improvement in students’ career decision making ability. It was proven by the data before they learned the Android-based interactive multimedia (M = 86.89; SD = 19.76) and after learning the Android-based interactive multimedia (M = 109.71; SD = 11.36; t(35) = -9.328, p < 0.05). These findings conclude that Android-based interactive multimedia is effective to improve the ability of students’ career decision making on career information services given to the Tenth Grade Level students of SMA 1 Kudus. Also, this study clarifies that the career information services by using interactive multimedia are applicable to students in career decision making.